Center-Pivot-Irrigated Dry-Edible Bean Cost-Return Budget in Western Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Holman, John; Haag, Lucas; Falk Jones, Jeanne (My University, 2015)
This publication projects a budget that reflects expected income and costs based on typical center-pivot-irrigated dry-edible bean production practices in western Kansas.
MF998_2015_04
Keywords: MF999; Economics; Crops; MF